2008
DOI: 10.1037/0012-1649.44.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in the relationship between parenting and children's behavior.

Abstract: Parent and teacher data for 14,990 children from the National Longitudinal Survey of Children and Youth were used in multilevel analyses to examine the relationship between ethnicity, children's aggression and emotional problems, and parenting. Using parent and teacher report, relationships between ethnicity and child behavior were present but modest. The association between parental harshness and child aggression differed between ethnic groups and across informants. Using teacher report of outcomes, parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 87 publications
2
57
0
Order By: Relevance
“…Specifically, harsh discipline is more strongly linked to child aggression among European Americans than among African Americans (Deater-Deckard, & Dodge, 1997;Lansford, 2010). This pattern --strongest links for European origin children --also emerged from a population-based sample of Canadian families (Ho et al, 2008). This robust finding does not hold true for all cultural comparisons, however.…”
Section: Parenting In Cultural Contextmentioning
confidence: 59%
“…Specifically, harsh discipline is more strongly linked to child aggression among European Americans than among African Americans (Deater-Deckard, & Dodge, 1997;Lansford, 2010). This pattern --strongest links for European origin children --also emerged from a population-based sample of Canadian families (Ho et al, 2008). This robust finding does not hold true for all cultural comparisons, however.…”
Section: Parenting In Cultural Contextmentioning
confidence: 59%
“…However, when mother-reported child externalising problems were evaluated , significant relationships were found for both European-American and African-American. Similarly, Ho et al (2008), using teacher-reports, showed a positive relationship between parental harshness and parent-rated child aggression among European Canadians, but not among Southern Asian Canadian families. Likewise, in the study by Yang et al (2014) no statistically significant results were found using teacher-reported behavioural problems; however, several correlations were reported between parenting styles and behavioural problems when using parent's statements.…”
Section: Discussionmentioning
confidence: 99%
“…Normality of the data was reported in the study of Aunola and Nurmi, (2005) and Braza et al, 2013). Missing data were reported in 5 studies (Deater-Deckard et al, 1996;Lansford, Deater-Deckard, Dodge, Bates, & Pettit, 2004;Ho et al, 2008;McKee et al, 2007;Yang et al, 2014).…”
Section: Setting Sample Size Ses Normality and Missing Datamentioning
confidence: 99%
See 2 more Smart Citations